Análisis y determinación de la fijación de nitrógeno a través de la siembra de mucuna (Stizolobium aterrimum), KUDZÚ (Pueraria phaseoloides) y maní forrajero (Arachis pintoil) en la zona de Quevedo. - Parrales Quintana, Marlon Orlando (2015)
This research was conducted at the "LA MARIA" in the Draft Organic Fertilizers, Faculty of Agricultural Sciences, State Technical University of Quevedo (UTEQ), located at km 7 track Quevedo- El Empalme, during the months of August 2013 to March 2015. The research had as general objective "Assessing nitrogen fixation of legumes in study to determine the highest amount of contribution", and as specific: Analyze soil quality in treatments with performing chemical and biological analysis. Analyze nitrogen fixation to improve eroded soils. Determine nitrogen fixation of legumes in research. Set the transformation of organic matter in legumes decomposition .....